PEMEKATAN PROTEIN DALAM SUSU DAN KECAP MENGGUNAKAN MEMBRAN SERAT BERONGGA - Syahril Ahmad (Research Center for Chemistry - LIPI, 2009)
Concentration of protein which found in freshmilk, sweet ketchup and salt ketchup have been done byusing hollow fiber polysulfone membrane with differentmolecular weight cut - off (MWCO). Membranes usedin these experiments have MWCO 66,000, 87,000 and 149,000 Dalton. Experimental were conducted bycontinues flow system and parameters observed in these experimental were protein, sugar and salt, respectively.Protein infresh milk rejected by membrane above 98 %,but all of sugar pass through to the permeate side. Forsweet ketchup feed sample, rejection coefficient towardsprotein was smaller than feed fresh milk. The higherrejection coefficientfor sweet ketchup was 48 % for themembrane with MWCO 66.000 Dalton. Rejectioncoefficient of membrane towards protein for salt ketchup sample was smaller than sweet ketchup sample. For saltketchup, the higher rejection coefficient towards proteinwas 27 % for the membrane with MWCO 66,000Dalton. Rejection coefficient of membrane towardsNaCl for feeding solution sweet ketchup and saltketchup were in the rlJ.1Jgefrom 8.74 to 23.96 %.Key words : Hollow fiber membrane, ultrafiltration, protein,milk, ketchup.